Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo:Nowa Era
Rok wydania:2015
Rozwiąż równanie 4.71 gwiazdek na podstawie 7 opinii

`a)` 

`(3-x)^2-(x+1/3)^2=2/9` 

`9-6x+x^2-(x^2+2/3x+1/9)=2/9` 

`9-6x+x^2-x^2-2/3x-1/9=2/9` 

`8 8/9-6 2/3x=2/9` 

`80/9-20/3x=2/9\ \ \ \ \ |*9` 

`80-60x=2\ \ \ \ |-80` 

`-60x=-78\ \ \ \ |:(-60)` 

`x=(-78)/(-60)=78/60=13/10=1,3` 

 

 

`b)` 

`4(1/2x-3)^2=(2-x)^2` 

`4(1/4x^2-3x+9)=4-4x+x^2` 

`x^2-12x+36=4-4x+x^2\ \ \ \ \ |-x^2` 

`-12x+36=4-4x \ \ \ \ |+12x` 

`36=4+8x\ \ \ \ \ |-4` 

`32=8x\ \ \ \ \ |:8` 

`x=4` 

 

 

 

`c)` 

`(6+1/3x)(-1/3x+6)+(1/3x-4)^2=4` 

`(6+1/3x)(6-1/3x)+(1/9x^2-8/3x+16)=4` 

`36-1/9x^2+1/9x^2-8/3x+16=4` 

`52-8/3x=4\ \ \ \ |-52` 

`-8/3x=-48\ \ \ \ |:(-8)` 

`1/3x=6\ \ \ \ |*3` 

`x=18` 

 

 

`d)` 

`(-4x-3)(4x-3)+8(1-sqrt2x)^2=1` 

`-(4x+3)(4x-3)+8(1^2-2*1*sqrt2x+(sqrt2x)^2)=1` 

`-(16x^2-9)+8(1-2sqrt2x+2x^2)=1` 

`-16x^2+9+8-16sqrt2x+16x^2=1` 

`17-16sqrt2x=1\ \ \ \ \ \ |-17` 

`-16sqrt2x=-16\ \ \ \ \ \ |:(-16sqrt2)` 

`x=(-16)/(-16sqrt2)=1/sqrt2=sqrt2/(sqrt2*sqrt2)=sqrt2/2`    

` `